Sunday, March 24, 2019
Home > Theory Of Computation > Conversion Of E-NFA To DFA

Conversion Of E-NFA To DFA

Conversion Of E-NFA To DFA

Let M=(Q,Σ,δ,q0,F) Be The NFA

M1=(Q1,Σ,δ1,q01,F1) Be The Equivalent DFA

 

1) Initial State:- 

q0– ε-Closure(q0)

2) Construction Of δ1

δ1(q,x)=ε-Closure(δ(q,x))

Start The Construction Of δWith Initial State And Continue For Every New State.

3) Final State:-

Every Subset Which Contain The Final State Of ε-NFA Is Final State Of DFA

 

Example:-

1)  Initial State:-

q01=ε-Closure(q0)

={q0,q1}

q0=q0,q1

2)

DFA

 

10 thoughts on “Conversion Of E-NFA To DFA

Leave a Reply

Your email address will not be published. Required fields are marked *